Contradiction - Jaivin, Linda; Klein, Esther Sunkyung (China Story Yearbook, 2022)
In the second year of the COVID-19 pandemic, the many facets of crisis-the theme of last year's China Story Yearbook-fractured into pictures of contradiction throughout Chinese society and the Chinese sphere of influence. Contradiction: the ancient Chinese word for the concept holds within it the image of an unstoppable spear meeting an impenetrable shield. It describes a wide range of phenomena that English might express with words like conflict, clash, paradox, incongruity, disagreement, rebuttal, opposition, and negation. This year's Yearbook presents stories of action and reaction, of motion and resistance. The theme of contradiction plays out in different ways across the different realms of society, culture, environment, labour, politics, and international relations. Great powers do not necessarily succeed in dominating smaller ones. The seemingly irresistible forces of authoritarianism, patriarchy, and technological control come up against energised and surprisingly resilient means of resistance or cooptation. Efforts by various authorities to establish monolithic narrative control over the past and present meet a powerful insistence on telling the story from an opposite angle. The China Story Yearbook: Contradiction offers an accessible take on this complex and contradictory moment in the history of China and of the world.